Utilization and Policy recommendation to The traditional herbal conservation: Case study Salung – Keelek Community, Mae Rim District, Chiang Mai Province - Jitae, Samart; Sommanee, Chatchaya; Jinasuk , Worawut; Thumjai, Patita (Community and Social Development Journal, 2021)
The purposes of mixed methods were to 1) study of traditional herbal utilization 2) Analysis of predictive factors between traditional herbal utilization of people and 3) Synthetic of the policy recommendation for traditional herbal conservation. Sample size was 301 households and 18 Interested people in Saluang-Keelek community, Maerim District, Chiangmai Province. Data collected by questionnaires, non - structured interviews and focus group discussion were executed. Data was analyzed by descriptive statistics, content analysis and multiple regression analysis. The results indicated that the utilization of traditional herbal was in a low level (mean = 1.98 ± 0.45). The significantly influenced factors of utilization of traditional herbal of people was perception towards utilization of traditional herbal (Beta = .265 , p - value = .000). This factor had predictive value of 26.7 %. The public has made policy recommendations to traditional herbal conservation by 1) conserve for traditional herbal resource 2) conserve for traditional herbal diversity 3) transmission activities about traditional herbal conservation and 4) the roles of government adding.